A System Integration Analysis of a Molten Carbonate Electrolysis Cell as an Off-Gas Recovery System in a Steam-Reforming Process of an Oil Refinery - Monforti Ferrario, Andrea; Santoni, Francesca; Della Pietra, Massimiliano; Rossi, Mosè; Piacente, Nicola; Comodi, Gabriele; Simonetti, Luca (Frontiers in Energy Research, 2021)
Technologies capable of efficiently exploiting unavoidable CO2 streams, synergically with renewable energy sources, have to be deeply investigated and deployed during the transition phase to achieve long-term climate neutrality targets. Among them, Molten Carbonate Cells (MCC) operating in electrolysis mode represents a promising equipment to valorize CO2-rich waste streams, which are typically available in industrial plants, by their conversion into high-value H2/CO syngas. These products can be reintegrated in the plant or reused in different applications. This study analyses the system integration of a MCC, operating in electrolysis mode under different operating conditions in terms of current, density and fuel utilization, in a steam reforming process of an Italian oil refinery via a mixed experimental-simulative approach. The aim of the present study is to assess the improvement of the overall plant efficiency by increasing the product yield. Results showed that is possible to obtain an electrochemical Specific Energy Consumption for H2 production of 3.24 kWh/Nm3H2 using MCEC, whereby the integration of 1MWe module with the reformer of the proposed plant is possible not only to increase the hydrogen yield but also to decrease the amount of fuel needed to assist the reforming reaction consequently determining lower greenhouse gases emissions.